Benzodiazepine Use among Chronic Pain Patients Prescribed Opioids: Associations with Pain, Physical and Mental Health, and Health Service Utilization. Issue 2 (3rd October 2014) - Nielsen, Suzanne; Lintzeris, Nicholas; Bruno, Raimondo; Campbell, Gabrielle; Larance, Briony; Hall, Wayne; Hoban, Bianca; Cohen, Milton L.; Degenhardt, Louisa
Abstract Objective Benzodiazepines (BZDs) are commonly used by chronic pain patients, despite limited evidence of any long‐term benefits and concerns regarding adverse events and drug interactions, particularly in older patients. This article aims to: describe patterns of BZDs use; the demographic, physical, and mental health correlates of BZD use; and examine if negative health outcomes are associated with BZD use after controlling for confounders. Subjects A national sample of 1, 220 chronic noncancer pain (CNCP) patients prescribed long‐term opioids. Methods We report on baseline data from a prospective cohort study comparing four groups based on their current BZD use patterns. General demographics, pain, mental and physical comorbidity, and health service utilization were examined. Results One‐third (N = 398, 33%) of participants reported BZD use in the past month, and 17% (N = 212) reported daily BZD use. BZD use was associated with: 1) greater pain severity, pain interference with life, and lower feelings of self‐efficacy with respect to their pain; 2) being prescribed "higher‐risk" (>200 mg oral morphine equivalent) doses of opioids; 3) using antidepressant and/or antipsychotic medications; 4) substance use (including more illicit and injection drug use, alcohol use disorder, and daily nicotine use); and 5) greater mental health comorbidity. After controlling for differences in demographic characteristics, physical and mental health, substance use, and opioid dose, BZD use was independently associated with greater past‐month use of emergency health care such as ambulance or accident and emergency services. Conclusions CNCP patients using BZDs daily represent a high‐risk group with multiple comorbid mental health conditions and higher rates of emergency health care use. The high prevalence of BZD use is inconsistent with guidelines for the management of CNCP or chronic mental health conditions.